The Preparation and Characterization of A Co-Processed Excipient from Purple Sweet Potato (Ipomoea batatas L) Starch and Avicel PH101 - Muhammad Hengki Purnama Halim; Ungsari Rizki Eka Purwanto; Endang Diyah Ikasari (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
The Indonesian pharmaceutical industries still rely on imports for more 90% of active raw materials and excipient raw materials. A research is needed to develop the production of pharmaceutical excipients, especially those derived from natural ingredients, to support the country's economy. One source of natural materials are widely available in Indonesia and can be developed is starch from Purple Sweet Potato (Ipomoea batatas L). Starch is often used as dilluent, disintegrat and binder in tablet formulation. Starch, including starch from Purple Sweet Potato, was an excipient tablet that had bad flowability and compressibility, so that the physical properties need to be improved. One way to improve the characterization of amilum is co-processing. The purpose of this study was to develop a co-process from Purple Sweet Potato Starch and combined with Avicel PH 101 as excipient fillers for tablets. The method used in the preparation of these co-process was wet granulation. The formula determination was caried out with Design Expert 10.0.1 software. Results obtained from experiments and recommendation formula from Design Expert 10.0.1 was verified with One Simple T-test with confidence level of 95%. Based on the results it can be concluded that the increased concentration of purple sweet potato starch increased moisture content and lowering compressibility and density. While the increased concentration of Avicel PH 101 increased compressibility and density; it could lower moisture content and the flowability time. The formula that gave the best characteristic of co-processed was obtained at a concentration of purple sweet potato starch and Avicel PH 101 on 62.493%: 37.507%. Based on One Simple T-Test, there is no significant difference between the experimental results with recommendation formula from Design Expert 10.0.1. From the FT-IR test results may indicate that the formation of the co-process did not change the form of the chemical structure of substances, but only changed the physical properties of substance. Based on the results of SEM, the morphology of the shape bond formation co-process so that the granules become larger and purple sweet potato starch forms a round and partly change shape after do the heating at 60°C. Keyword : Co-processing, Purple_Sweet_Potato, Starch, Avicel_PH101, FTIR